Disaster declarations and their effects on the most valuable seasonal crops of Veracruz: Most valuable seasonal crops of Veracruz and their relationship with disaster declarations - Valdés-Rodríguez, Ofelia Andrea (Ecosistemas y Recursos Agropecuarios, 2025)
Seasonal crops are more susceptible to hydrometeorological phenomena, and the Veracruz state is vulnerable to them since many disaster or emergency declarations (DD) are registered. However, an analysis of these phenomena and the agricultural productivity and losses linked to them has yet to be explored. This research aims to determine the effects of DD on the productivity and losses of the ten more valuable of the 12 more productive municipalities of the state during the 2003-2022 period. Municipal production data against disaster or emergency declaration (DD) were correlated with the Spierman test (P ≤ 0.05). Results indicate that corn has the most damaged land, statistically significant for tropical cyclones, rains, floods, and droughts. Pineapple has the highest economic losses, which are statistically significant with floods. Sugar cane, which has the highest state value, is also the less vulnerable to DD. It is concluded that the ten more valuable crops are vulnerable to the hydrometeorological phenomena in the 12 more productive municipalities, with the higher implications in crops with higher value by surface. With higher citrus, coffee, and potato production in the north, they are more vulnerable to tropical cyclones and rains. At the same time, in the south, with higher production of sugar cane and pineapple, they are more susceptible to tropical cyclones, rains, and floods.